Air-Turbine with Self-Pitch-Controlled Blades for Wave Energy Conversion (Estimation of Performances in Periodically Oscillating Flow). (1997) - Setoguchi Setoguchi, T. T.; Raghunathan Raghunathan, S. S.; Takao Takao, M. M.; Kaneko Kaneko, K. K.
Abstract : In the development of an air-turbine with self-pitch-controlled blades for wave energy conversion, existence of hysteretic characteristics in a reciprocating flow has been examined. In order to clarify the validity of the analysis, a numerical simulation has been made by use of the experimental results obtained from a steady unidirectional flow condition. The comparison between the analysis and experiment has shown that the quasi-steady analysis is reasonable accurate for predicting the performance. The running and starting characteristics have also been investigated analytically taking into account the blade turning process during pitch.